Behavioral intervention on nonpharmacological pain management for child : a systematic review - Wesiana; Ugrasena; Yuni Sufyanti; Nur Hidayah; Resti Utami (Bali medical journal, 2022)
Introduction: Children should not only be managed in high pain conditions; pain management in children should also involve moderate procedures, particularly invasive. Behavioral intervention is pain management for children since it is invasive action. The study's objective was to examine how behavioral therapies were used to treat children's discomfort without the use of drugs. Method: We used PRISMA principles and conducted a systematic review. The original keywords utilized were "child," "behavioral treatment," and "pain management," which were further developed using "medical subject headings." Scopus, PubMed, and Research Gate were the three databases that were searched for prospective papers published between 2000 and 2020. Results: Children can experience less pain by engaging in behavioral interventions like joyful pingu pain relief, cognitive behavioral therapy, positive reinforcement, graphic books about intravenous placement for training the desired behavior, and watching their favorite music videos. Conclusion: Children can experience less pain with the help of behavioral therapies like happy pingu, cognitive behavioral therapy, picture books about intravenous placement, and watching their favorite music videos. These interventions train the desired behavior and can also be used to stop discomfort.